Aménager les bas-fonds ? D'accord, mais comment ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Aménager les bas-fonds dans les pays du Sahel. Coédition CTA/GRET/ Coopération française, 1998, 528 pages. ISBN 2-86844-099-1, n° CTA 897, 40 unités de crédit